Development and characterization of thermal insulation materials from renewable resources. (30th July 2019) - Viel, Marie; Collet, Florence; Lanos, Christophe
Highlights: Two bio-binders are obtained by extraction process on corn cob and on flax fine. Development of wholly bio-based composites with hemp shiv and corn cob residues is investigated. The mechanical properties are sufficient to ensure self-bearing. Thermal conductivity of composites is low enough to use them as insulating materials. Composites show high Moisture Buffer Value. Abstract: The present study has investigated the scope for valuation of agro-resources by-products as aggregates and as binding material to produce rigid fully bio-based composite panels. Two types of aggregates: hemp shiv and corn cob residues (obtained after alkali treatment on the corn cob), and six types of green binders are investigated. Specimens are produced to verify the gluing effect, to characterize mechanical, thermal and hygric properties of developed composites and to identify the best aggregate-binder mixture. They show interesting thermal conductivity ranging from 67 to 148 mW/(m.K) at dry state, excellent hygric properties (MBV > 2 g/(m 2 ).%RH)) and high enough mechanical properties to be self bearing. These results suggest that developed composites can be used as building materials but not for the same types of use. In fact, some composites would be more suitable for thermal insulating products and others would be better suited for indoor facing panels.